PENGARUH HUMAN CAPITAL, ECONOMIC FREEDOM, DAN CAPITAL FORMATION TERHADAP PEMBANGUNAN EKONOMI ISLAM DI NEGARA-NEGARA OKI - Indirwan, Syanisma; Susanto, Arva Athallah; Herianingrum, Sri; Widiastuti, Tika; Robani, Anidah Binti (Jurnal Ekonomika dan Bisnis Islam, 2025)
This study aims to analyze the influence of human capital, economic freedom, and capital formation on Islamic economic development in the member countries of the Organization of Islamic Cooperation (OIC). Using a quantitative approach with panel data from nine OIC countries over the period 2002–2023, the study employs a multi-method panel regression model, including Pooled OLS, Fixed Effect, Random Effect, PCSE, and System GMM. The Human Development Index (HDI) is used as a proxy for Islamic economic development, while the independent variables include dimensions of human capital (MYS and LE), economic freedom (LABF, MONF, TRAF, INVF, FINF), and capital formation (GCF). The analysis results show that variables such as Life expectancy, Gross capital formation, Monetary freedom, and Financial freedom consistently have a significant positive effect on HDI in most models, while variables such as Trade Freedom, Investment Freedom, and Mean Years of Schooling show inconsistent or insignificant effects. This study highlights the importance of synergy between human investment policies, macroeconomic stability, and the Islamic financial system in fostering sustainable and socially just economic growth in the Islamic world. The policy implications of these findings encourage strengthening the health sector, spiritually oriented education, and inclusive Islamic financial governance to accelerate the achievement of the Sustainable Development Goals (SDGs) in OIC countries.